Single candidate and the dynamics of 2020 Indonesian Simultaneous Election: A perspective on internal contestation - Romli, Lili; Efriza, Efriza (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
This paper describes the development of local-level democracy in implementing the 2020 Regional Head Simultaneously related to a single candidate and dynastic politics. In this research, we found that the phenomenon of single candidates and political dynasties, which shows the climate of democracy at the local level, is increasingly unhealthy. Indonesia is experiencing democratic backsliding. Political dynasties and single candidates have, of course, hurt democracy. Regional Head is no longer an effective means of participation and competition as a condition for the running of democracy. Regional Head also did not produce elite circulation. On the other hand, the oligarchy is a node on a political dynasty and local bossism. The theoretical perspectives used in the research to explain single candidates and political dynasties are democracy, election, oligarchy, and local bossism.